2011
DOI: 10.1055/s-0031-1291176
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin: Dose-Response Relationship in Generalized Anxiety Disorder

Abstract: Implications for psychiatric practice, limitations of the methodology and avenues for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Ginseng total saponin showed dose-dependent, incremental antihyperalgesic effects in the incisional pain model [3] . However, in the present study, ginsenoside Rf-MWT had a curvilinear-shaped dose–response relationship, similar to pregabalin, buprenorphine, and haloperidol, the effects of which were more pronounced at medium rather than high dosages [32] , [33] , [34] . The peak effective dose of ginsenoside Rf in the present study was 1.5 mg/kg, and achieved a significant antinociceptive effect.…”
Section: Discussionmentioning
confidence: 78%
“…Ginseng total saponin showed dose-dependent, incremental antihyperalgesic effects in the incisional pain model [3] . However, in the present study, ginsenoside Rf-MWT had a curvilinear-shaped dose–response relationship, similar to pregabalin, buprenorphine, and haloperidol, the effects of which were more pronounced at medium rather than high dosages [32] , [33] , [34] . The peak effective dose of ginsenoside Rf in the present study was 1.5 mg/kg, and achieved a significant antinociceptive effect.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to safety data contained in the clinical trials cited above, four additional citations summarised results of studies with safety as the primary outcome (Frame et al, 2009; Hindmarch et al, 2005a, 2005b; Rubio et al, 2011). Finally, 11 review articles were identified that specifically evaluated the safety and efficacy of pregabalin in the treatment of GAD (Bandelow et al, 2007; Bech, 2007; Boschen, 2011, 2012; Frampton and Foster, 2006; Holsboer-Trachsler and Prieto, 2013; Lauria-Horner and Pohl, 2003; Montgomery, 2006; Montgomery and Kasper, 2010; Owen, 2007; Wensel et al, 2012). These articles were each reviewed to determine whether they contained additional citations not identified in the MEDLINE and PsychINFO literature searches.…”
Section: Methodsmentioning
confidence: 99%
“…In this concept of the dose-response relationship, an agent may often show inhibitory activity at higher doses [32]. Many drugs, such as haloperidol, buprenorphine, cannabidiol, and pregabalin, show a bell-shaped dose response [33,34,35,36]. Although this concept cannot sufficiently be explained in this paper, this dose-response relationship indicates that a response could only be achieved at a certain concentration, and this could make it difficult to use Rg3 clinically as a single agent.…”
Section: Discussionmentioning
confidence: 99%